Do guidelines help us to deviate from their recommendations when appropriate for the individual patient? A systematic survey of clinical practice guidelines. Issue 3 (17th June 2019) - Morgott, Marc; Heinmüller, Stefan; Hueber, Susann; Schedlbauer, Angela; Kühlein, Thomas
Abstract: Rationale, aims, and objectives: Clinical practice guidelines (CPG) were introduced to summarize the best scientific evidence available. Thereby, CPG were meant to support evidence‐based medicine (EBM). However, besides evidence, EBM also asks for patients' preferences and physicians' experiences to be considered when coming to therapeutic decisions. Thus, deviations from CPG recommendations are sometimes necessary when practicing EBM. We wanted to examine whether CPG support deviations from their recommendations when appropriate. For operationalization, we asked whether absolute effect sizes (AES) for benefit and/or harm of suggested therapies were provided along with the respective CPG recommendation. Methods: This systematic survey comprised the most common CPG on chronic coronary heart disease (CCHD) and type 2 diabetes mellitus (T2DM) from English‐ and German‐speaking countries. Only CPG recommendations on pharmacotherapy were evaluated. If AES of a recommended therapy were reported, we rated how easily findable they were within the CPG. Moreover, we assessed whether the CPG provided patient information material and whether this material supplied AES allowing patients to determine the effects to be expected. Results: In the 13 CPG surveyed, 144 recommendations on pharmacotherapy were identified. For 108 recommendations (75%), no AES for benefit and/or harm were reported. Thirty‐one recommendations (22%) were accompanied by one or more AES for either benefit or harm. Along with five recommendations (3%), one or more AES for both benefit and harm were given. AES were considered easy to find for three of these 36 recommendations (8%). Patient information material was provided in three of the 13 CPG (23%) accounting for AES in one occasion only. Conclusion: Current CPG on T2DM and CCHD do not sufficiently offer AES for benefits and harms of recommended therapies. Thus, they lack satisfactory information to support deviations from CPG recommendations. Consequently, CPG in their present form do not adequately facilitate EBM.